b&emath

# b&emath - lc=-2 const=9 b-t 1 –(t 1 =-t 1 – t-1...

This preview shows pages 1–3. Sign up to view the full content.

Erin Stancick Economics 156 Midterm Exam 1 1. Evaluate the expression if m= 2, n= -3 and p= 25 a) 5p(n+3m ) = 5(25) (-3+3(2) ) = 125(-3+3(4)) = 5 x 25 x 9 = 1125 b) (2n-3m) = (2(-3)-3(2)) = (-6-6 ) = -12 p 25 5 5 c) |6-(-5)|+|12-24| = 11+12 = 23 2. Write the expression without using absolute value a) |-2-18| = -(-2-18) = 20 b) | a-9 | if a < 9 = | a-9 | = -(a-9) = -a+9 3. Compute the following (leave it with exponents). a) ((5z ) ) = (5z x z ) = ( 5 ) x ( z ) = 5 x z b) [a a ] = [a a ] = [ a ] = a c) 2 (2 + 2 ) = 2 x 2 + 2 x 2 = 2 + 2 4. Find the following, determine degree, leading coefficient, and the constant

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
a) (-2p -5p +7) + (-4p +8p + 2) = -2p -4p +3p +9 deg= 3
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: lc= -2 const=9 b) (-t +1) – (t +1) = -t +1 – t -1 = -2t deg= 3 lc= -2 const= 0 c) (-t +1)(t +1) = -t -t + t +1 = -t +1 deg= 6 lc= -1 const = 1 d) 2p(3 + 3p )(3p + 5) = (6p + 6p )(3p + 5 ) = 5. Factor the polynomial a) x + 10x + 24 = (x + 4)(x + 6) b) v - 64 = (v + 8)(v – 8) c) y -4yzc – 21z c = (y + 3zc)(y – 7zc) d) x -8 = x +2 (x -4) = (x ) -2 = ( x -2)( x + 2x +4) 6. Simplify a) y(y + 1) y = y(y+1) 3 = 3(y + 1 ) = (3y + 3) y 3 y y y y b) 4x + 8 3w = (4x + 8)(3w ) = 4 (x + 2) 3w = 12w = 12w w x+2 w (x + 2) w (x + 2) 1 c) 4(x-1) _ 3x = 4x – 4 _ 3x = x-4 = x - 2 = 2x x+1 2(x-1) x + 1 2x – 2 2x - 2 2x - 1...
View Full Document

## This note was uploaded on 07/25/2011 for the course ECON 156 taught by Professor Amin during the Spring '11 term at Bloomsburg.

### Page1 / 3

b&emath - lc=-2 const=9 b-t 1 –(t 1 =-t 1 – t-1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online